The need for extended intensive care after pancreaticoduodenectomy for pancreatic ductal adenocarcinoma - Welsch, Thilo; Degrate, Luca; Zschäbitz, Stefanie; Hofer, Stefan; Werner, Jens; Schmidt, Jan (Langenbeck's archives of surgery, 2011)
Pancreaticoduodenectomy (PD) is standard for patients with resectable pancreatic ductal adenocarcinoma (PDAC) in the pancreatic head, neck, and uncinate process, but it is associated with a relatively high morbidity. This study aimed to identify risk factors for extended postoperative intensive care unit (ICU) admission and assess the impact of ICU treatment on patient survival.